Pharmacological Treatment of Headache - Filho, Luciano Barbosa de Sousa Santos; Nogueira, Guilherme Nobre; Pereira, Maria Clara Moura; Almeida, Giovanna Sean Gregório Pereira; Gonçalves, Rafaela Fernandes; Aragão, Gislei Frota (Headache Medicine, 2023)
Full abstract in PDF.